Lipoxygenase ‐ trypsin inhibitor activity axis induction in the host plants of muga silkworm, Antheraea assamensis Helfer by feeding. Issue 10 (22nd August 2021) - Mech, A.; Choudhury, K.K.; Bora, DS
Abstract: The muga silkworm, Antheraea assamensis Helfer bears great economic importance, producing golden yellow muga silk which is in global demand for both the textile and biomedical industries. The insect's larval stages are maintained in the field by farmers on its primary host plant Persea bombycina Kost in Assam located in the North‐East part (25.57 ° N, 93.25 ° E) of India. If continuous feeding by A. assamensis is inducing any direct defense in P. bombycina, the aspect is not yet questioned. We used the activity of lipoxygenases (LOX) and trypsin inhibitors as markers for determining defense responses in P. bombycina and Litsea monopetala Roxb, the two primary host plants of the silkworm due to insect feeding. The induction of anti‐herbivore trypsin inhibitor by insect feeding was examined by studying their effect on the midgut trypsin activity of A. assamensis larvae. This is the first report showing that the LOX‐ trypsin inhibitor axis is differentially activated in the two host plants and greater induction of the defense response is exhibited in P. bombycina, the most commercially used host plant in muga silkworm rearing.